Maximizing Polyphenol Content to Uncork the Relationship Between Wine and Cancer - Champ, Colin E.; Kundu-Champ, Anjali (Frontiers in Nutrition, 2019)
Studies have revealed conflicting results regarding the risk of cancer from alcohol consumption. Furthermore, some studies have suggested that wine may have benefits that separate it from other alcoholic beverages. As wine contains a significant amount of chemicals, specifically polyphenols like anthocyanins and proanthocyanidins (PA), that can affect cellular function and promote health, this hypothesis is reasonably supported by recent research. Polyphenols promote several anticancer cellular pathways, including xenobiotic metabolism, support of innate antioxidant production, and stimulation of phase I and II detoxification of carcinogens. However, the multitude of growing and production conditions of grapes, including temperature, water availability, soil type, maceration, and aging can result in a remarkably varying final product based on the available literature. Thus, we hypothesize that wines produced from grapes cultivated between steady daily temperatures at 15-25⁰C with moderate sun exposure from flowering to harvest, lower vine-water status, resulting either from lower precipitation, and irrigation practices or more permeable soil types, limitation of fertilizers, extended maceration, and aging in oak will impact the concentration of anthocyanins and PA in the finished wine and may have a differential impact on cancer. This higher concentration of polyphenols would, in theory, create a healthier wine, thus explaining the conflicting reports on the benefits or harms of wine.